Parabolic turbulence k-epsilon model with applications in fluid flows through permeable media - Oliveira, Hermenegildo Borges de (Wydawnictwa AGH, 2024)
In this work, we study a one-equation turbulence $k$-epsilon model that governs fluid flows through permeable media. The model problem under consideration here is derived from the incompressible Navier-Stokes equations by the application of a time-averaging operator used in the $k$-epsilon modeling and a volume-averaging operator that is characteristic of modeling unsteady porous media flows. For the associated initial- and boundary-value problem, we prove the existence of suitable weak solutions (average velocity field and turbulent kinetic energy) in the space dimensions of physics interest.
Opuscula Mathematica
Bibliogr. 238-240.
Keywords: turbulence; k-epsilon modelling; permeable media; existence